Incorporation of Nonyl 3,4-Dihydroxybenzoate Into Nanostructured Lipid Systems: Effective Alternative for Maintaining Anti-Dermatophytic and Antibiofilm Activities and Reducing Toxicity at High Concentrations - Costa-Orlandi, Caroline Barcelos; Serafim-Pinto, Aline; da Silva, Patrícia Bento; Bila, Níura Madalena; Bonatti, Jean Lucas de Carvalho; Scorzoni, Liliana; Singulani, Junya de Lacorte; Santos, Claudia Tavares dos; Nazaré, Ana Carolina; Chorilli, Marlus; Regasini, Luis Octávio; Fusco-Almeida, Ana Marisa; et al. (Frontiers in Microbiology, 2020)
Dermatophytosis is the most common mycosis worldwide, affecting approximately 20 to 25% of the population, regardless of gender, race, color and age. Most antifungal agents used for the treatment of dermatophytosis belong to the azole and allylamine classes. Dermatophytes are reported to be resistant to most commercial drugs, especially microbial biofilms, in addition to their considerable toxicity. It should be emphasized the importance of looking for new molecules with reduced toxicity, as well as new targets and mechanisms of action. This work aims to incorporate nonyl 3,4-dihydroxybenzoate, a potent fungicide compound against planktonic cells and dermatophyte biofilms in nanostructured lipid systems (NLS), in order to reduce toxicity in high concentrations, improve its solubility and maintain its effectiveness. The compound was incorporated into NLS constituted by cholesterol, mixture of polyoxyethylene (23) lauryl ether (Brij®98) and soybean phosphatidylcholine (Epikuron® 200)], 2: 1 ratio and PBS (phosphate-buffered saline). The characterization of the incorporation was performed. Susceptibility tests were conducted according to document M38-A2 by CLSI (2008). The toxicity of the NLS compound was evaluated in HaCaT cell lines by the sulforhodamine B method and in alternative models Caenorhabditis elegans and zebrafish. Finally, its efficacy was evaluated against the mature Trichophyton rubrum and Trichophyton mentagrophytes biofilms. NLS and nonyl 3,4-dihydroxybenzoate loaded into NLS displayed sizes ranging from 137.8 ± 1.815 to 167.9 ± 4.070 nm; the polydispersity index (PDI) varying from 0.331 ± 0.020 to 0.377 ± 0.004 and zeta potential ranging from –1.46 ± 0.157 to –4.63 ± 0.398 mV, respectively. Polarized light microscopy results confirmed the formation of NLS of the microemulsion type. Nonyl incorporated into NLS showed minimum inhibitory concentration (MIC) values, ranging from 2 to 15.6 mg/L. The toxicity tests presented cell viability higher than 80% in all tested concentrations, as well as, a significantly increased of the survival of Caenorhabditis elegans and zebrafish models. Anti-biofilm tests proved the efficacy of the incorporation. These findings contribute significantly to the search for new antifungals and allow the systemic administration of the compound, since the incorporation can increase the solubility of non-polar compounds, improve bioavailability, effectiveness and reduce toxicity.